Marginalised Identity in Timberlake Wertenbaker’s Play: New Anatomies - Ülker Erkan, Ayça B. (Journal of History Culture and Art Research, 2017)
The purpose of this study is to discuss the space for a marginalized feminine identity in contemporary British feminist dramatist Timberlake Wertenbaker’s play. The play New Anatomies dramatizes the life of a historical woman called Isabelle Eberhardt, who disguised herself as an Arab man called Si Mahmoud living among Algerians. The focus of the play is the construction of a marginalised identity through dislocation of a woman from the European culture. Finding no space for her radical identity, she disguises herself as an Arab man to escape the constraints imposed on women by European ideals of femininity. Eberhardt disrupts the conventional gender codes by showing how gender is dramatized within the space of the salon. In contrast, Eberhardt is received as a man in male attire when travelling in Algeria trying to find out a space for her radical identity. She achieves a certain kind of freedom by her dislocation although this eventually leads to her death in desert.